Zwitterionic nanoparticles constructed from bioreducible RAFT–ROP double head agent for shell shedding triggered intracellular drug delivery. (August 2016) - Huang, Pingsheng; Liu, Jinjian; Wang, Weiwei; Zhang, Yumin; Zhao, Fuli; Kong, Deling; Liu, Jianfeng; Dong, Anjie
Graphical abstract: Abstract: Nanomedicines have emerged as indispensable platforms for cancer theranostics, however, the therapeutic outcomes were often compromised not only by the multiple biological barriers during the itinerary from the initial injection site to the intracellular action site but also the insufficient drug release at the pathological site. Herein, novel bioreducible double head agent, combining reversible addition-fragmentation chain transfer agent and ring opening polymerization initiator through disulfide linkage, was firstly prepared. Well-defined cRGDfK-polycarboxybetaine methacrylate-SS-polycaprolactone block copolymers (termed as cRGD-PCSSL) were facilely synthesized using this initiator. Subsequently, shell sheddable and drug-encapsulated zwitterionic nanoparticles were constructed by one-step self-assembly with doxorubicin (DOX) (termed as cRGD-PCSSL/DOX NPs). The reduction-responsive shedding of PCB shells resulted in the rapid loss of cRGD-PCSSL/DOX NPs stability in the presence of glutathione, facilitating the rapid DOX release. Results of flow cytometry and fluorescence microscopy demonstrated that cRGD-PCSSL/DOX NPs could be internalized by HepG2 cells via receptor-mediated endocytosis with fast intracellular drug release, leading to considerable cytotoxicity in comparison with free DOX. Importantly, the low protein adsorption and excellent serum stability properties of cRGD-PCSSL/DOX NPs translated into prolonged systemic circulation and enhanced tumor accumulation. Furthermore, intravenous injection of cRGD-PCSSL/DOX NPs in tumor-bearing mice exhibited significantly higher antitumor efficiency and lower systemic toxicity compared to free DOX. Consequently, the novel zwitterionic NPs, which facilely overcome the dilemma between multifunctionality and complexity by programmatically circumventing the multiple biological barriers, would represent a promising platform for enhanced anticancer drug delivery. Statement of significance: Herein, novel bioreducible RAFT and ROP double-head agent was first reported for the synthesis of cRGDfK-polycarboxybetaine methacrylate-SS-polycaprolactone zwitterionic block copolymers (cRGD-PCB-SS-PCL, termed as cRGD-PCSSL) through controllable polymerization methods. Firstly, this synthetic route surmounted the major disadvantage of most current used methods, which required thiol exchange reaction between active disulfide bond and free thiol groups at the chain ends. Secondly, the prepared cRGD-PCSSL/DOX NPs reasonably integrated cRGD for active tumor targeting and receptor-mediated endocytosis, zwitterionic PCB with nonfouling property for prolonged systemic circulation, disulfide linkage for reduction-responsive drug release, biodegradable PCL for hydrophobic anticancer drug loading. Finally, the systematic evaluation fully verified that the in vitro optimized cRGD-PCSSL/DOX NPs translated into significantly better therapeutic efficiency with reduced side effects in vivo .